LBA observations of OH masers in the star-forming region OH 330.953-0.182 - Kramer B.H. (2014)
OH masers are sensitive probes of the kinematics, physical conditions, and magnetic fields in star-forming regions. The maser site OH 330.953-0.182 has been studied using the Long Baseline Array of the Australia Telescope National Facility. Simultaneous observations of the 1665- and 1667-MHz hydroxyl ground-state transitions yield a series of maps at velocity spacing 0.09kms 1, in both right- and left-hand circular polarization, with tenth-arcsec spatial resolution. Several clusters of maser spots have been detected within a five-arcsec region. Eight Zeeman pairs were found, and in one case, at 1665 MHz, there is a nearby 1667-MHz pair indicating a similar value of magnetic field and velocity. Over the whole site, all magnetic field estimates are toward us (negative), and range from -3.7 to -5.8 mG. We also compared the morphology and kinematics of the 1665- and 1667-MHz maser spots with those from the excited state of OH at 6035 MHz and from methanol at 6668 MHz. © 2008 International Astronomical Union.